Pertanggungjawaban Tindak Pidana Perbankan Perspektif Hukum Pidana dan Undang-Undang Perbankan - Anggar Ramadhani Yudhistira; Nur Handayani; Wahyu Prawesthi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Criminal acts in the banking sector are defined as all types of unlawful acts related to activities in carrying out bank business activities and intersect with the provisions of laws and regulations containing special criminal law and general criminal law. The purpose of this study is to determine the Accountability for Banking Crimes from the Perspective of Criminal Law and Banking Law. Using the Normative Juridical method.The practice or mode of violation of the bank procedure system carried out by bank employees and resulting in banking crimes is carried out with the following characteristics: Banking crimes are always followed by violations of the bank procedure system.In the event of a violation of the bank procedure system and resulting in a crime in the banking sector, the bank as a corporation cannot be held criminally responsible for the crime committed by bank employees because of banking laws and regulations, especially Article 49 of Law No. 10 of 1998 limits the perpetrators to individuals only, namely Directors, Commissioners or Bank Employees. In the event that the impact of the act is detrimental to the bank's customers concerned, then the responsibility that can be demanded of the bank as a corporation is civil responsibility.